EXPERIMENTAL JUSTIFICATION OF THE ABSORBER SELECTION FOR THE PROCESS OF SIMULTANEOUS CHEMISORPTION OF HYDROGEN SULPHIDE AND CARBON DIOXIDE - Botagoz M. Kaldybayeva,; Alisher E. Khussanov,; Arlan Zh. Abilmagzhanov,; Stanislav Boldyryev, (Academic Journal of Physical and Chemical Sciences, 2019)
In this article, the objects of research are combined membrane-absorption processes with a chemical reaction and chemisorption plants for the purification of multicomponent gas mixtures. The subject of the research were the processes of removal of H2S and CO2 from multicomponent gases. The results of studying the features of simultaneous absorption of H2S and CO2 by an aqueous solution of NaOH are carried out. With the subsequent analysis and selection of the main parameters of the extraction process of H2S. With the simultaneous absorption of H2S and CO2, it is established that the chemical capacity of the absorption solution decreases with respect to H2S. The rate and concentration constants for the absorption of H2S and CO2